2018
DOI: 10.1016/j.jshs.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The association of various social capital indicators and physical activity participation among Turkish adolescents

Abstract: BackgroundPhysical activity participation (PAP) has been proven to improve health and promote optimal growth among adolescents. However, most adolescents do not meet the current physical activity (PA) recommendations in Turkey. The role of the social environment and social factors on PAP is being increasingly recognized. Although social capital (SC) indicators have been examined in high-income countries, there are few studies on developing countries. The aim of this study was to examine the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 49 publications
3
10
1
6
Order By: Relevance
“…Regarding regular physical activity of the students, as per their statements only 25.1% engaged in regular sportive or physical activity. This finding was in accordance with the World Health Organization (WHO) report, which indicated that 77.1% of male and 86.9% of female young adults in Turkey led a physically inactive lifestyle [24].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding regular physical activity of the students, as per their statements only 25.1% engaged in regular sportive or physical activity. This finding was in accordance with the World Health Organization (WHO) report, which indicated that 77.1% of male and 86.9% of female young adults in Turkey led a physically inactive lifestyle [24].…”
Section: Discussionsupporting
confidence: 91%
“…The answers were binarized into “high” (strongly agree and agree) and “low” (neither agree nor disagree, disagree, and strongly disagree) social capital [49]. These items have been previously used in the studies examining relationships of social capital and physical activity among adolescents of Turkey [40] and Croatia [42], examining relationships of social capital and self-rated health among adolescents in Serbia [50] and Lithuania [51] and in combined sample of European adolescents [52].…”
Section: Methodsmentioning
confidence: 99%
“…However, to the best of our knowledge, there is no scientific evidence that social capital influences adolescents’ eating behavior, and no study has examined the importance of social capital on healthy eating, in general, and with regard to adhering to an MD, in particular. However, several attempts have been made to investigate the relationships among social capital and physical activity [40,41,42] and substance use [43,44,45,46] in adolescents. Although the evidence strongly suggests that high levels of social capital enhance physical activity in adolescents, the results have not been very consistent in regard to social capital and substance use.…”
Section: Introductionmentioning
confidence: 99%
“…Regular exercise training (ET) has been considered to be the most effective intervention in preventing and reducing CVDs (Romeo et al, 2018). Exercise, which is considered the most effective, accessible, and inexpensive therapy a physician can prescribe, aids in blood pressure control, improves blood lipid profiles, and increases insulin sensitivity (Günay et al, 2018).…”
Section: Introductionmentioning
confidence: 99%